Volume 2B: Advanced Manufacturing 2015
DOI: 10.1115/imece2015-51349
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Steel Friction Stir Welding: Project HILDA

Abstract: Friction stir welding of steel presents an array of advantages across many industrial sectors compared to conventional fusion welding techniques. Preliminary studies have identified many positive effects on the properties of welded steel components. However, the fundamental knowledge of the process in relation to structural steel remains relatively limited, hence industrial uptake has been essentially non-existent to this date. The European-funded project HILDA, the first of its kind in terms of breadth and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In single-sided FSW, temperatures >773 K have been recorded in the machine bed. 31 These temperature effects could explain the distinct differences in observed microstructures of TMAZ and IZ. However, if the highest temperature of IZ remains below Ar 1 , a problem arises in explaining the observation in Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In single-sided FSW, temperatures >773 K have been recorded in the machine bed. 31 These temperature effects could explain the distinct differences in observed microstructures of TMAZ and IZ. However, if the highest temperature of IZ remains below Ar 1 , a problem arises in explaining the observation in Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Thomas et al [10] demonstrated the feasibility of FSW of steels in 1999 on a 12% chromium alloy and a low carbon steel. Since then, several authors addressed this subject, including studies in numerical modelling [11,12] and economic analysis [13]. FSW was considered superior to conventional fusion welding in many categories, although tooling costs and limited service life are viewed as obstacles to a faster uptake by industry.…”
Section: Introductionmentioning
confidence: 99%
“…Although friction stir welding (FSW) has been extensively researched for joining steel alloys [1][2][3] and aluminum alloys [4][5][6][7], the industrial application of polymer FSW is still under consideration due to several limitations [8,9]. These mainly include the weld strength, potential defects and optimal process parameters to obtain a good-quality weld [10,11].…”
Section: Introductionmentioning
confidence: 99%